A (re)construção de identidades do ser americano moderno e a criação simbólica de arturo uslar pietri: diálogos entre literatura e história - SILVA, Gisele Reinaldo da (Universidade Federal do Pará, 2020)
This paper aims to reflect about the role of the new historical romance contemporary, regarding the (re) construction of modern American identities, based on the work El Camino de El Dorado, from the Venezuelan writer Arturo Uslar Pietri (1947). When referring to the period of the Spanish Conquest of America, guided by the force of the Amazon River, Uslar Pietri embarks on a symbolic journey into the civilization history o in the Western world, towards the discovery of purely local, inserted into the universal. The author implies himself, in the context of Spanish-American literature of the twentieth century, seeking an individual and collective identity that best contribute to the historical and cultural understanding of his country, Venezuela and, more broadly, the American individual identity. It will be also necessary for the development of this paper, the essayistic wide basis in the author's work (1949, 1955, 1969, 1991).